Examining context shifts' effect on relationship trajectories in friendships using Turning Point Theory. (June 2020) - Dominguez, Jess; Hall, Jeffrey A.
Drawing from Turning Point Theory, this study explores whether context shifts, which are changes in the location where a friendship is enacted, affect relationship trajectories and friendship closeness. Study 1A ( N = 120) experimentally manipulated invitations for context shifts in college friendships to test their effects on perceived relationship trajectory, social attraction, and closeness. Study 1B ( N = 112) replicated the results of Study 1A with working adults. Both studies' results suggest that context-variable shifts lead to a change in perceived relationship trajectory but did not influence social attraction or closeness. In Study 2, first-year students ( N = 98) reported on turning points in their friendships twice over 9 weeks. Friendships reporting context-variable shifts as a turning point were associated with higher friendship closeness than relationships that had no turning points and similar closeness as friendships that reported self-disclosure as a turning point.